The unexpected role of calcium-activated potassium channels: limitation of NO-induced arterial relaxation - Schmid, Johannes A.; Müller, Bettina; Heppeler, David; Gaynullina, Dina; Kaßmann, Mario; Gagov, Hristo; Mladenov, Mitko; Gollasch, Maik; Schubert, Rudolf (Journal of the American Heart Association, 2018)
Background: Multiple studies have shown that an NO‐induced activation of vascular smooth muscle BK channels contributes to the NO‐evoked dilation in many blood vessels. In vivo, NO is released continuously. NO attenuates vessel constrictions and, therefore, exerts an anticontractile effect. It is unknown whether the anticontractile effect of continuously present NO is mediated by BK channels.Methods and ResultsThis study tested the hypothesis that BK channels mediate the vasodilatory effect of continuously present NO. Experiments were performed on rat and mouse tail and rat saphenous arteries using isometric myography and FURA‐2 fluorimetry. Continuously present NO donors, as well as endogenous NO, attenuated methoxamine‐induced vasoconstrictions. This effect was augmented in the presence of the BK channel blocker iberiotoxin. Moreover, the contractile effect of iberiotoxin was reduced in the presence of NO donors. The effect of the NO donor sodium nitroprusside was abolished by an NO scavenger and by a guanylyl cyclase inhibitor. In addition, the effect of sodium nitroprusside was reduced considerably by a protein kinase G inhibitor, but was not altered by inhibition of H2S generation. Sodium nitroprusside attenuated the intracellular calcium concentration response to methoxamine. Furthermore, sodium nitroprusside strongly reduced methoxamine‐induced calcium influx, which depends entirely on L‐type calcium channels. It did not affect methoxamine‐induced calcium release.ConclusionsIn summary, this study demonstrates the following: (1) continuously present NO evokes a strong anticontractile effect on rat and mouse arteries; (2) the iberiotoxin‐induced augmentation of the effect of NO is associated with an NO‐induced reduction of the effect of iberiotoxin; and (3) NO evoked a reduction of calcium influx via L‐type calcium channels.
Published online 2018 Mar 24
Gesehen am 26.03.2020